2024
DOI: 10.3390/ijms25020938
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Electroporation versus Electrochemotherapy with Bleomycin in an In Vivo CAM-Based Uveal Melanoma Xenograft Model

Theodora Tsimpaki,
Ralitsa Anastasova,
Hongtao Liu
et al.

Abstract: Despite recent advancements in the diagnosis and treatment of uveal melanoma (UM), its metastatic rate remains high and is accompanied by a highly dismal prognosis, constituting an unmet need for the development of novel adjuvant therapeutic strategies. We established an in vivo chick chorioallantoic membrane (CAM)-based UM xenograft model from UPMD2 and UPMM3 cell lines to examine its feasibility for the improvement of selection of drug candidates. The efficacy of calcium electroporation (CaEP) with 5 or 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
0
0
Order By: Relevance
“…This model, involving the engrafting and propagation of human tumor materials in zebrafish hosts, holds promise for personalized medicine applications [ 299 ]. In addition, the use of the chick embryo chorioallantoic membrane (CAM) model, already established for UM fundamental research [ 300 ], showed recently a potential for an effective and economical model for preclinical assessment, as well as for enhancing the selection of drug candidates and developing new effective treatment strategies for UM [ 301 ]. Interestingly, BAP1 -deficient Xenopus laevis embryos were used previously for a drug screening and allowed to identify the HDAC4 inhibitor quisinostat as a candidate for the treatment of BAP1 -mutant UMs [ 302 ].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…This model, involving the engrafting and propagation of human tumor materials in zebrafish hosts, holds promise for personalized medicine applications [ 299 ]. In addition, the use of the chick embryo chorioallantoic membrane (CAM) model, already established for UM fundamental research [ 300 ], showed recently a potential for an effective and economical model for preclinical assessment, as well as for enhancing the selection of drug candidates and developing new effective treatment strategies for UM [ 301 ]. Interestingly, BAP1 -deficient Xenopus laevis embryos were used previously for a drug screening and allowed to identify the HDAC4 inhibitor quisinostat as a candidate for the treatment of BAP1 -mutant UMs [ 302 ].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%